AKM; Inovasi Evaluasi Pembelajaran Menyongsong Pendidikan Global - Sri vamiati; Hendro Prasetyono (STKIP Subang, 2026)
The Minimum Competency Assessment (AKM) as one of the National Assessment instruments is a new policy innovation in learning evaluation in Indonesia which is expected to improve the quality of education and the competence of students in facing global challenges. However, the fact is that this policy has not been socialized properly at every level of the education unit. The purpose of this study is to provide a holistic understanding of the AKM concept and its implementation at the education unit level as part of the National Assessment. The method used is library research. The results of this study obtained empirical facts that the AKM is an innovation in a national assessment designed to measure reading literacy and mathematical literacy (numeracy). Literacy AKM is used to measure the ability to understand, use, evaluate and reflect on various types of texts to solve problems and develop individual capacities as citizens of Indonesia and citizens of the world so that they can contribute productively to society, meanwhile AKM numeracy is implemented to measure the ability to think using concepts, procedures facts, and mathematical tools to solve everyday problems in contexts that are relevant to individuals as citizens of Indonesia and the world.